Carbohydrate And Energy Content Of Soybean Hulls Soaked In Husk Ash Water Filtrate (FAAS) - Ginting, Risdawati; Sembiring, Meriksa; Sri Setyaningrum; Puteri Wahyu Lestari (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the energy and carbohydrate content of soybean hulls soaked with husk ash water filtrate (FAAS). The study used an experimental method with a randomized complete block design (RAL) Factorial, Factor I; the concentration of husk ash water filtrate consists of F1: 10%, F2: 20% and F3: 30%. The second factor is the length of soaking time consisting of W1: 24 hours, W2: 48 hours, and W3: 30 hours. Each treatment was repeated three times. Based on the results of statistical analysis showed that there was no interaction (P<0.05) between the concentration of FAAS and the length of soaking time on the Energy and Carbohydrate values of soybean hulls.